Generalized disaggregation algorithm for the vehicle routing problem with time windows and multiple routes - Macedo, Rita (2012)
In this paper, we address the VRP with multiple routes and time windows. For this variant of the VRP, there is a time interval within which every customer must be visited. In addition, every vehicle is allowed to perform more than one route within the same planning period. Here, we propose a general disaggregation algorithm that improves the exact approach described in (Macedo et al., 2011). We describe a novel rounding rule and a new node disaggregation scheme based on different discretization units. We describe a new integer programming model for the problem, which can be used, with a slight modification, to exactly assess whether a given solution is feasible or not. Finally, we report some computational experiments performed on a set of instances from the literature.